Censorship detected in GB (United Kingdom) - Voidly (2025)
CRITICAL severity censorship detected in United Kingdom. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: GB-2025-0001
Keywords: censorship; GB; censorship; critical